Screening of fetal chromosomal aneuploidy diseases using noninvasive prenatal testing in twin pregnancies. (1st February 2019) - Yu, Wenqian; Lv, Yuan; Yin, Shaowei; Liu, Hao; Li, Xue; Liang, Bo; Kong, Lingyin; Liu, Caixia
ABSTRACT: Objectives : This study was aimed to report the clinical characteristics of fetal chromosomal aneuploidy diseases using noninvasive prenatal testing (NIPT) in twin pregnancies and analyze the results in terms of chorionicity, conception, and fetal fraction. Methods : A total of 1160 women with twin pregnancies were recruited from 1 October 2015, to 1 August 2017. Next-generation sequencing technology was used to detect fetal aneuploidies, such as trisomy 21, trisomy 18, trisomy 13 and trisomy X. Results : Aneuploidy was detected using NIPT in 26 fetuses, among which 18 fetal aneuploidies occurred in only one fetus of the twins. The rate of aneuploidy was 1.3% for dichorionic diamniotic twins and 0.5% for monochorionic diamniotic twins, respectively. The rate of aneuploidy was 1.2% for spontaneous pregnancy group and 1.1% for assisted reproductive technologies group. Conclusion : In this study, detection of trisomy 21, trisomy 18, trisomy 13, and X abnormality in twin pregnancies was confirmed to be accurate. The aneuploidies mostly occurred in only one fetus of the twins, and trisomy 21 was the most common type. The prenatal diagnostic standard for NIPT in singleton pregnancies could perform well in twin pregnancies, which means NIPT can be popularized as routine prenatal screening in twin pregnancies.